ASSESSMENT OF TYPE C IN CHRONIC PATIENTS - Anarte, María Teresa; López, Alicia Eva; Ramírez Maestre, Carmen; Esteve Zarazaga, Rosa (Anales de Psicología / Annals of Psychology, 2000)
Several researches have studied the role of personality factors in disease onset and progression. The question whether or how personality may influence the onset and course of disease has been a subject of popular interest for many years and, in the last 20 years, of scientific inquiry. A number of studies which employ various methodologies have described the Type C Personality Style that appears to be related to cancer onset and progression. The aim of this research is to study the specificity of the Type C in relation to cancer. So we assessment the Type C with the Type C Personality Questionnaire (Amorós, Anarte, Esteve, López y Ramírez, 1998; Esteve, López, Anarte, Ramírez y Amorós, 1998; López, Esteve, Ramírez y Anarte, 1998) in two samples of chronic patients (100 with cancer and 103 with diabetes) and we analyze the differences between the samples. We found differences between cancer patients and healthful subjects (Control, Rationality, Need of Harmony, and the Total of the Scale), between diabetes patients and healthful subjects (Control, Repression and Need of Harmony) and between cancer patients and diabetes patients (Control, Rationality, Need of Harmony and the Total of the Scale). So, we can say that the “Type C” is not specific of cancer patients. It's possible that the Type C personality construct is a behavior standard multidimensional specific of patients with chronic disease. Future research will replicate current findings on cancer disease samples.